2020
DOI: 10.1007/s42452-020-03957-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reduction reaction kinetics on pure copper in neutral sodium sulfate solution

Abstract: Oxygen reduction reaction (ORR) kinetics were investigated on different copper surface conditions in 10-2 M Na 2 SO 4 solution. On pre-reduced and passivated copper surfaces, the ORR is suggested to occur by a parallel pathway involving HO 2 − formation followed by its diffusion to the solution or rapid reduction to OH −. A significant difference in ORR activity is observed in the kinetic and mixed control regions as copper surface becomes more oxidized. On a surface covered by ammonium pyrrolidine dithiocarba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
(110 reference statements)
4
10
0
Order By: Relevance
“…The technique has been used in multiple electrochemical investigations and provides information on the oxide composition and thickness (e.g., amount per unit area) via the establishment of reduction plateau's that can be assigned to a specific oxide species. [ 26–33 ] Data are presented in Figure a, where the potential (V vs SCE), resulting from cathodic galvanostatic holds at −20 µAcm −2 , is plotted as a function of time. Four distinct plateau regions can be observed in all experiments where AM was present in the pre‐exposure (labeled 1, 2, 3, and 4 in Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique has been used in multiple electrochemical investigations and provides information on the oxide composition and thickness (e.g., amount per unit area) via the establishment of reduction plateau's that can be assigned to a specific oxide species. [ 26–33 ] Data are presented in Figure a, where the potential (V vs SCE), resulting from cathodic galvanostatic holds at −20 µAcm −2 , is plotted as a function of time. Four distinct plateau regions can be observed in all experiments where AM was present in the pre‐exposure (labeled 1, 2, 3, and 4 in Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The same conclusion was drawn in previous investigations employing CR in comparable conditions. [ 32,33 ] Employing Equation (), the data infers that the reduction of CuO occurs at a potential of −0.233 V versus SCE relative to the equilibrium potential for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxidation species generated from O 2 and in particular H 2 O 2 are likely to play a role herein. We recently have shown that the reduction of peroxide mediated by Cu(tmpa) most likely proceeds via a Fenton like mechanism wherein ROS are involved [22a] . It is unclear which species along the path from Cu 2 (btmpa) to dep Cu is responsible for the high ORR rates leading to selective formation of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We recently have shown that the reduction of peroxide mediated by Cu(tmpa) most likely proceeds via a Fenton like mechanism wherein ROS are involved. [22a] It is unclear which species along the path from Cu 2 (btmpa) to dep Cu is responsible for the high ORR rates leading to selective formation of H 2 O 2 . However, it is clear that this is not the final species in the sequence.…”
Section: Resultsmentioning
confidence: 99%
“…j L and j K are the diffusion and kineticlimiting current densities, n is the transferred electron number, F is the faraday constant (96485 C mol À 1 ), Co 2 is the concentration of oxygen in an oxygen-saturated solution (0.5 M Na 2 SO 4 ) (12.6 × 10 À 7 mol cm À 3 ), Do 2 is the diffusion coefficient of O 2 (1.9 × 10 À 5 cm 2 s À 1 ), and ν is the kinetic viscosity (1.01 × 10 À 2 cm 2 s À 1 ). [59][60] The constant 0.62 is used when the rotation speed is expressed in rad s À 1 . Figure 7d shows the ring current recorded in the RRDE experiment in 0.5 M Na 2 SO 4 .…”
Section: Chemistryselectmentioning
confidence: 99%